2017
DOI: 10.7710/2168-0620.1099
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Attitudes toward Debt

Abstract: This work has undergone a double-blind review by a minimum of two faculty members from institutions of higher learning from around the world. The faculty reviewers have expertise in disciplines closely related to those represented by this work. If possible, the work was also reviewed by undergraduates in collaboration with the faculty reviewers. AbstractFraternity and sorority members are overrepresented as perpetrators and victims of sexual assault, respectively. The current study examined rape myth acceptanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(88 reference statements)
2
6
0
Order By: Relevance
“…Researchers who previously investigated the link between financial knowledge and financial attitudes obtained mixed results. For example, Beale and Cude () report a lack of any significant relationship, while Lachance () and Almenberg et al () document a positive association. The current study showed that the debt attitudes of adult Poles are linked to debt literacy—that is, both debt knowledge and debt skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers who previously investigated the link between financial knowledge and financial attitudes obtained mixed results. For example, Beale and Cude () report a lack of any significant relationship, while Lachance () and Almenberg et al () document a positive association. The current study showed that the debt attitudes of adult Poles are linked to debt literacy—that is, both debt knowledge and debt skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, in light of the existing empirical evidence, the effect of gender on financial literacy is much more puzzling than other characteristics of sociodemographic and economic status. The effect of gender on financial literacy, the “gender gap” in favour of male individuals, has been found many times in empirical research not only in financial literacy tests (Alessie, Rooij, & Lusardi, ; Beckmann, ; Brown & Graf, ; Disney & Gathergood, ; Gentile, Linciano, & Soccorso, ; Klapper & Panos, ; Lusardi & Mitchell, ; Sekita, ; Stolper & Walter, ; The Freedom Institute and Raiffeisen Polbank, ) but also in financial attitudes, including attitudes towards debt (Almenberg et al, ; Beale & Cude, ; Haultain et al, ). For this reason, this study focuses on gender as a particularly interesting factor determining debt attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of these students were funded by education loans, whilst those with academic achievements and other fields may have been offered scholarships and others sponsored by parents (Norhaslinda Daud, Norlia Mat Norwani, Rohaila Yusof, 2018). Issues on whether these funding were spent appropriately may have been brought into the spotlights several times (Beale & Cude, 2017;eMarketer, 2014;Paul, Nolan, & Smith-Hunter, 2017;Sorooshian & Teck, 2014;Wang & Xiao, 2009). Concerns in regards to the sufficiency of these financial aids and how it was utilized, were given many attentions (Abdullah & Ibrahim, 2007;Avery & Turner, 2012;Beale & Cude, 2017;Ismail & Zainal, 2004;Lynch, Best, Gutierrez, & Daily, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Issues on whether these funding were spent appropriately may have been brought into the spotlights several times (Beale & Cude, 2017;eMarketer, 2014;Paul, Nolan, & Smith-Hunter, 2017;Sorooshian & Teck, 2014;Wang & Xiao, 2009). Concerns in regards to the sufficiency of these financial aids and how it was utilized, were given many attentions (Abdullah & Ibrahim, 2007;Avery & Turner, 2012;Beale & Cude, 2017;Ismail & Zainal, 2004;Lynch, Best, Gutierrez, & Daily, 2018). However, interpreting the word 'need' itself may have been diverse due to varying lifestyles and perceptions on money.…”
Section: Introductionmentioning
confidence: 99%